SOME GRAMMATICAL FEATURES OF THE SGFI BASED ON THE MATERIAL OF THE STENOGRAMS OF THE SESSIONS OF THE VERKHOVNA RADA OF UKRAINE - Леонова, Наталья (SWorldJournal, 2021)
The work examines the grammatical features of the SGFI (small genre forms of information) based on the transcripts of the meetings of the Verkhovna Rada of Ukraine, their specificity and frequency of use in these analyzed texts. The position of modern li